KONSEP DIRI ANGGOTA DEWAN PERWAKILAN DAERAH REPUBLIK INDONESIA (DPD – RI) PADA KONTEKS KOMUNIKASI ANTARBUDAYA - Teuku Yuliansyah (Ilmu Komunikasi, FISIP Universitas Pasundan, 2022)
Indonesia is multicultural, which means that it does not only recognize the plurality of certain ethnic groups or cultures, but also emphasizes equality between these cultures. The existence of ethnicity should be considered as the nation's essential wealth that can be used to form social relations, to enrich the nation's cultural assets. In this case, multiculturalism accommodates two (2) things that are contradicted, namely 'Difference' and 'Equality'. Thus, despite the high level of heterogeneity,